Gestão governamental, disputa política e opinião pública: análise da produção de conteúdo da pandemia pela COVID-19 em portais de notícias - Nunes, Carlo Endrigo Bueno (2021)
Within the scope of Government Management, among the various affects experienced by the occurrence of the state of public calamity by SARS-CoV-2, the theme of this study refers to the relationship between Public Management, political dispute, public opinion formation and production of media content on the news portals about the Covid-19 pandemic. The research in relation to the influence of the production of media content in the formation of public opinion puts Government Management in focus to face the crisis generated by the pandemic, whose object of this study concerns the media contents of Covid-19 made available in the news portals more accessed in Brazil (globo.com, Notícias.uol and r7.com) and to public opinion polls conducted by Datafolha. The main objective of the research is to analyze the power of influence of the media in the public opinion, through the mapping of the content production of the news portals about the pandemic by Covid-19 and of the public opinion polls in the period from March to December 2020, thus allowing to relate them with the interactions between this dispute and the acts of the federal public management, in order to be able to analyze them qualitatively. As for the methodology, it is a case study, whose method used is of the type documentary research, of a descriptive, qualitative and exploratory nature. From a universe of 2,859 articles published on the three websites, of which 1,213 are content productions about the pandemic, whose sample consists of 33 news items and, as for public opinion polls, the search on the Datafolha website resulted in 75 opinion polls public actions undertaken by the institute around the pandemic. The results obtained point to the reflection of the media discourse in the formation of public opinion, evidencing the influential power of the production of content of the mass communication vehicles in public opinion polls, acting as agents that transform the published opinion, directly influencing the construction of the society's point of view on the topic at hand. It can be concluded that, in the news portals, the production of news content illustrates Covid-19's media exposure, whose spectacularization goes far beyond the act of informing, being related to the process of forming public opinion.